“SARS-CoV-2 infection of endothelial cell, clinical laboratory and autopsy findings, and outcomes suggest role of hypoxia-inducible factor-1 in COVID-19”: Hypothesis to explain features of COVID-19 - Ambade, Vivek (Journal of Medical Biochemistry, 2021)
Researchers around the world have experienced the dual nature of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), ‘tragically lethal in some persons and surprisingly benign in others’. They have congregated to study novel coronavirus disease (COVID-19), a disease that mainly attacks the lungs, but also has mystifying effects on the heart, kidneys and brain. Researchers are also gathering information to determine what actually kills COVID-19 patients, whether respiratory disorder or coagulation disorder or multi organ failure. Various laboratory parameters like lactate, ferritin, hypoalbuminemia have been established as risk factor or associated with poor outcomes, but yet could not be substantiated with the scientific biochemical rationale. SARS-CoV-2 affects the alveolar type II epithelial cells, that significantly disturbs its surfactant homeostasis, deprive Na,K-ATPase of  ATP, thereby  disturbing the alveolar lining fluid which then gradually decreases the alveolar gaseous exchange  initiating intracellular hypoxic conditions. This activates AMP-activated kinase, which further inhibits Na,K-ATPase, that  can  progressively cause  respiratory distress syndrome.The virus may infect endothelial cell (EC), which being low energetic, cannot withstand the huge energy requirement towards viral replication,  and therefore glycolysis,  the prime energy generating pathway,  has to mandatorily be upregulated, which can be achieved by Hypoxia-inducible factor 1 (HIF-1). However, HIF-1 activates transcription of von Willebrand factor, plasminogen activator inhibitor-1, and suppresses the release of thrombomodulin, thereby setting off the coagulation cascade that leads to in-situ pulmonary thrombosis and micro clots.The proposed HIF-1 hypothesis can rationalize various features, clinical laboratory as well as autopsy findings such as respiratory distress syndrome, increased  blood ferritin and lactate levels, endothelial invasion, in-situ pulmonary thrombosis and micro clots,  and multiorgan failure in COVID -19Keywords: novel coronavirus, COVID-19, SARS-CoV-2, severe acute respiratory syndrome coronavirus 2, hypoxia-inducible factor-1
Keywords: novel coronavirus, COVID-19, SARS-CoV-2, severe acute respiratory syndrome coronavirus 2, hypoxia-inducible factor-1